Analisis Pengetahuan dengan Kemampuan Keluarga Merawat Pasien Dalam Mengontrol Halusinasi Dirumah - Fatmawati Fatmawati; Syahrir Syahrir (Jurnal Ilmiah Kesehatan Sandi Husada, 2023)
For the patient's hallucinations to be interrupted, family support is needed, where family support is one of the interventions that can be done to increase patient compliance in treatment; of course, family support can be done if the family knows how to treat sick family members. This study aims to identify knowledge of families' ability to care for patients with hallucinatory problems. The research design used in this study is an analytical survey with a cross-sectional approach. The population is a family of 78 patients, with a total sample of 47 respondents taken by consecutive sampling. Data were processed using Fisher's Exact Test statistical test. The results obtained a test value between knowledge and family motivation p = 0.000, showing the p-value < α (0.05). It was concluded that there is a relationship between knowledge and the ability of families to care for patients to control hallucinations at home. So that families are expected to be able to apply the knowledge and information obtained at the hospital related to procedures for caring for family members who experience hallucinations and try to find information related to hallucinatory diseases and immediately seek help if there is no relapse